Atypical meningioma. - Magalhães, Z (2001)
One case of intradiploic meningioma, causing partial occlusion of the superior longitudinal sinus, with subsequent visual trouble and another of lipomatous meningioma with great fat content and very calcified, that was found in a LCR fistula study of the cranial anterior stage, are described by the authors as atypical meningiomas.